Legality of Interfaith Marriages in Indonesia: Legal Review, Implementation Management, and Psychological Impact on Families - Hasanudin, Hasanudin; Nurishlah, Laesti; Badruzaman, Dudi; Yudiyanto, Mohamad; Alputri, Misella (IJBLE Scientific Publications Community Inc., 2024)
This study aims to analyze the legality of interfaith marriage in Indonesia, including legal review, implementation management, and psychological impact on the family. The research method used is library research with a qualitative research approach. The study results show that policy recommendations must include changes to marriage laws, increasing public awareness, and education about the importance of tolerance and inclusivity in a multicultural society like Indonesia. The convoluted recording process and the inconsistency between state law and religious law are the main challenges that must be overcome. The implementation of the legality of interfaith marriage in Indonesia is still experiencing bureaucratic rigidity and a lack of coordination between related institutions. This creates administrative barriers that often prevent interfaith couples from obtaining official recognition of their marriage. Couples of different religions and their families experience significant psychological impacts, including social stigma, identity conflicts, psychological distress, and difficulties in educating children. This indicates the need for greater psychological and social support for interfaith couples